An Analytical Comparison of Soccer Academy Between Algerian and Tunisian professional team - GUEMINI, Hafid; ABDELLI, Fateh; MELAOUHIA, Sami Fouzi (Journal of Human Sciences, 2020)
The study aimed to shed light on one of the factors of the low level of Arab football in North Africa represented by Algeria and Tunisia, and its inability to prove itself Africa and Worldwide competition, because of the difficult reality that has become the advantage of national teams, whether it is the first teams or youth teams, as The advantage of these teams in the last decade has moved away from achieving coronations and only to reach and participate in African and international championships and intermittently. The reason for this, according to specialists and technical experts in both countries is the decline in the level of performance of the local player in the two professional tournaments, and the inability of the two schools to train players with specifications compatible with modern African and international football. The study was based on the field of football training in Algerian and Tunisian professional clubs and its success factors with comparing the situation in the teams of the two countries to show the differences and similarities between them and know the weaknesses and strengths of the training process adopted by professional teams. The study was conducted according to the descriptive and analytical method and the comparative approach by relying on a research sample of 23 trainers for youth groups in Algerian professional clubs and 15 trainers for the same categories in Tunisian professional clubs. The results of the research showed a significant imbalance of the factors of football formation in the Algerian professional clubs compared to its Tunisian counterpart, which recorded some of the positive.